Bifidobacterium animalis subsp. Lactis BX-BC08 modulates gut microbiota and secretes alpha-Ketoglutaric acid to alleviate MC903-induced atopic dermatitis - Jiamin Zhao; Ling Kui; Jinqun Huang; Jie Deng; Lingjun Liu; Chenwei Zhu; Yanqiang Shi; Chengyi Li; Yue Xiao; Jinshi Yu; Qing Li; Bin Yang; et al. (Journal of Translational Medicine)
Abstract Objective Bifidobacterium is known to be depleted in patients with atopic dermatitis (AD). This study aims to investigate the potential prophylactic effects of Bifidobacterium animalis subsp. lactis BX-BC08 (B. lactis BX-BC08) in a murine model of AD. Design The immunosuppressive and anti-inflammatory effects of BX-BC08 were evaluated in a MC903-induced AD mouse model. Gut microbiota composition was analyzed by metagenomic sequencing, while high-performance liquid chromatography-mass spectrometry (HPLC-MS) was employed to identify anti-inflammatory molecules produced by B. lactis BX-BC08. Results BX-BC08 significantly attenuated pro-inflammatory responses, scaling and swelling in the MC903-induced AD like murine model compared to controls. Fecal microbial profiling revealed an enrichment of probiotics and a reduction of pro-inflammatory bacteria in BX-BC08 treated mice. Metabolic analysis of BX-BC08 bacteria culture supernatant and treated mice identified a significant enrichment of alpha-Ketoglutaric acid (AKG). Functional validation in the murine AD model demonstrated that AKG strongly suppressed T helper 2 (Th2)-driven pro-inflammatory responses. Conclusion BX-BC08 mitigates AD-like inflammation by producing the anti-inflammatory metabolite AKG. BX-BC08 could serve as a novel prophylactic agent for AD prevention.